The Analysis of the Influencing Factors related to the Effectiveness of Discharge Planning Implementation in Hospitals: A Systematic Review - Hari Soebagiyo; Kornelis Nama Beni; Tan Nina Fibriola (Jurnal Ners, 2019)
Introduction: Discharge Planning is one of the agendas that is a part of nursing duties. This is not only complicated but it is also a long-term activity, starting from when the patients are admitted to hospital until they are allowed to go home. Factually, it cannot be denied that effective nursing discharge planning implementation will provide benefits for the patient, their family and the professionals within the health care setting. Based on those facts, the author composed this systematic review with the purpose of identifying the influential factors that have a role in terms of the effectiveness of nursing discharge planning implementation in hospitalsMethods: The researcher conducted their investigation in February 2019 and this involved the exploration of scientific papers from ProQuest and Scopus using the keywords ‘nursing discharge planning’, ‘effectiveness’ and ‘implementation’. This paper identified 15 relevant research articles from 500 original full texts. These papers were analyzed according to the inclusion criteria and the impeding factors in discharge planning implementation. It involved 1 quasi-RCT and 14 descriptive research studies.Results: As a result, from the 10.000 respondents, it was found that the enhancing factors include effective communication at 43% and the factors causing impedance in nursing discharge planning effectiveness includes the continuity of staff at 38 %.Conclusion: The dominant factor of impedance as stated in the interview sessions was a lack of time to do the nursing discharge planning properly.